Socio-economic and Policy Determinants of Low Fertility in OECD Countries (2014–2023): Implications for South Korea - Choi, Young-Chool; Ju, Sanghyun; Lee, Gyutae; Lee, Sangyup; Kim, Sangkun; Yun, Sungho (Journal of Posthumanism, 2025)
Low fertility rates pose significant demographic and economic challenges across many OECD countries, including South Korea. This study examines how economic, social, and policy-related factors collectively influence fertility decisions by employing fixed-effects regression models on panel data from 2014 to 2023. The findings confirm that higher unemployment rates and economic uncertainty negatively affect fertility, whereas family benefit expenditures and childcare support exhibit positive, statistically significant relationships with birth rates. Multidimensional Scaling (MDS) analysis further reveals distinct clusters among OECD countries, highlighting a group of Nordic nations that sustain relatively high birth rates alongside robust female labor force participation and comprehensive family policies. In contrast, South Korea stands out with a notably low fertility level and comparatively underdeveloped support structures, underscoring the urgent need for targeted policy interventions. Based on these results, the study proposes a comprehensive policy framework that integrates employment stability, enhanced childcare services, and culturally supportive environments to promote sustainable fertility outcomes. The study’s implications underscore not only the importance of aligning macro-level policies with micro-level sociocultural contexts, but also the particular relevance of such insights for addressing persistent low fertility rates in South Korea.